Seasonalities in China's Stock Markets : Cultural or Structural? - Mitchell, Jason; Ong, Li. (Washington, D.C. : International Monetary Fund, 2006)
In this paper, we examine returns in the Chinese A and B stock markets for evidence of calendar anomalies. We find that both cultural and structural (segmentation) factors play an important role in influencing the pricing of both A- and B-shares in China. There is some evidence of a February turn-of-the-year effect, partly owing to the timing of the Chinese Lunar New Year (CNY); and the holiday effect around the CNY period is stronger and more persistent compared with the other public holidays. The segmentation between the two markets is apparent in the day-of-the-week effect, where B stock markets tend to post significant negative returns on Tuesdays, corresponding with overnight developments in the United States, while significant negative returns are observed on Mondays in the A stock markets. Investment strategies based on some of these calendar anomalies, and allowing for transaction costs, suggest that the A stock markets tend to offer more economically significant returns.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: United States